Assessment of local tissue water in the arms and trunk of breast cancer survivors with and without upper extremity lymphoedema. (12th September 2018) - Mazor, Melissa; Smoot, Betty J.; Mastick, Judy; Mausisa, Grace; Paul, Steven M.; Kober, Kord M.; Elboim, Charles; Singh, Komal; Conley, Yvette P.; Mickevicius, Gabby; Field, Jennifer; Hutchison, Heather; et al.
Summary: Given the paucity of information on local tissue water (LTW) in the upper extremity and trunk of women after breast cancer surgery, the purpose of this study was to compare tissue dielectric constant (TDC) values between the affected and unaffected sides of breast cancer survivors with and without upper extremity lymphoedema (LE). Differences in LTW were assessed using the TDC method for three sites in the upper limbs, three sites in the lateral thorax and two sites on the back. Additional measures included demographic and clinical characteristics, arm circumference and bioimpedance analysis. For the 112 survivors without LE, no differences in TDC values were found between the affected and unaffected sides for the first dorsal web space, ventral forearm and upper arm, and upper and lower back. Compared to the unaffected side, TDC values were significantly higher on the affected side for the upper, mid and lower lateral thorax. For the 78 survivors with LE, compared to the unaffected side, TDC was significantly higher on the affected side for all of the sites evaluated except the hand web space. Our findings support the use of the TDC method to detect differences in upper extremity and truncal oedema in survivors with LE following breast cancer treatment. Measurement of LTW may provide a useful method to determine truncal as well as extremity LE. The ability to detect early signs of truncal oedema may lead to pre‐emptive interventions in breast cancer survivors.